A Brief Study of Paneer Dodi Plant: Phytochemical properties and Pharmacognostic Effects: Exploring the therapeutic potential of Withania coagulans plant extracts (Journal of Advances and Scholarly Researches in Allied Education, 2021)
A great vegetation have been said to cure various health problems and ailments in ancientsystems of medicine. Withania coagulans (W. coagulans) Dual ( also Paneer Dodi Plant) , also called as'Indian cheese maker'or'vegetable rennet,' is a medicinal plant belonging to the Solanaceae family. It is atiny gray-whitish shrub that grows eastern direction of the Mediterranean and into South Asia. In variousareas of Pak. and India, it is used as a medicinal plant. W. coagulans is commonly utilised in diabeticsituations in the Ayurvedic school of medicine. Nervous tiredness, incapacity, sleeplessness, wastingdisorders, inability to thrive in children, and impotence are all treated with W. coagulans. They're alsoused to treat liver problems, asthma, and biliousness. The active chemicals extracted from the plant, inparticular withanolides, are thought to have antibacterial, anti-inflammatory, anticancer,hepatoprotective, anti-hyperglycemic, cardiovascular, immuno-suppressive, free radical scavenging, andCNS depressing properties. This review focuses on Biological Processes involved in some of theisolated W. coagulans components, as well as phytochemistry and pharmacognostic aspects of plantextracts.